PERAN ETIKA KEPEMIMPINAN KRISTIANI TERHADAP GURU DI SD XYZ JAKARTA BARAT [THE ROLE OF ETHICS IN LEADERSHIP BASED ON CHRISTIAN VALUES FOR TEACHERS AT XYZ PRIMARY SCHOOL IN WEST JAKARTA] - Feryanto Munthe (Magister Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Pelita Harapan, 2021)
This research investigated the impact of leadership based on Christian values associated with leadership ethics and the connection between the ethics in leadership and teacher’s self-efficacy and organizational commitment. The research used the qualitative research method with phenomenology as the method. Data collection techniques were conducted by using interviews, observations, and documentation. The validity of the data was tested using triangulation. The research findings explained that the ethics of Christian leadership applied by the principal of SD XYZ through her working performance, provided an inspiration for the teachers to build high self-efficacy and created a community based on Christian values, which was love, with the result that the community became a comfortable working place to be committed to.